(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the growing significance of paralinguistics— non-verbal vocal cues such as tone, pitch, and intonation—in the field of humancomputer interaction (HCI). As artificial intelligence (AI) technologies advance, the ability of machines to interpret and utilize paralinguistic features becomes essential in creating more naturalistic, responsive, and emotionally aware systems. The study discusses the integration of paralinguistic cues in various applications, including voice assistants, emotion recognition interfaces, language learning tools, and virtual environments. It also addresses challenges related to cross-cultural interpretation, technical limitations, and ethical concerns. The article concludes by emphasizing the role of paralinguistics in the future of empathetic and socially aware computing.